2009
DOI: 10.1186/1471-2466-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of psychological and physiological predictors of fatigue in patients with COPD

Abstract: BackgroundFatigue in COPD impairs functional status; however there are few studies examining mechanistic pathways of this symptom. The aims of this study are to compare fatigue between COPD patients and healthy age-matched subjects, and to identify predictors of fatigue in COPD.MethodsSeventy four COPD patients, mean age 69.9 (49-87) yrs, mean (SD) % predicted FEV1 46.5 (20.0) % and FEV1/FVC ratio 0.45 (0.13) and 35 healthy subjects, mean age 67.1 (50-84) yrs completed the Multidimensional Fatigue Inventory (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 40 publications
(48 reference statements)
9
57
1
2
Order By: Relevance
“…Furthermore, the prevalence, experience (frequency, duration and severity) and the number of patients with no, moderate and severe fatigue was similar in men and women which is in agreement with previous studies [76][77] .…”
Section: Factors Associated With Low Physical Activitysupporting
confidence: 80%
“…Furthermore, the prevalence, experience (frequency, duration and severity) and the number of patients with no, moderate and severe fatigue was similar in men and women which is in agreement with previous studies [76][77] .…”
Section: Factors Associated With Low Physical Activitysupporting
confidence: 80%
“…Existing literature has shown that COPD patients report greater fatigue than the general population [35][36][37]. However, the severity of fatigue between COPD patients and other clinical populations has rarely been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue has been defined as "the multidimensional sensation of tiredness that the individual experiences when perceiving the reduced capacity to function normally" and it often varies with respect to daily pattern, triggers or contributing factors, and responsiveness to interventions (Kapella et al, 2006). In contrast with a prevalence rate of 18.3%-25% in the general population (Lewko et al, 2009;Pawlikowska et al, 1994) fatigue is "almost always" experienced by 43%-58% of persons with COPD ( Kinsman et al, 1983;Walke et al,2007).…”
Section: Introductionmentioning
confidence: 91%
“…The overall score of fatigue is calculated by adding all subscales, so that the overall score ranges from 20 to 100. A higher score implies more severe fatigue (Breslin et al, 1998;Lewko et al 2009;Meek & Lareau, 2003;Oh et al, 2004).…”
Section: Multidimentional Fatigue Inventory (Mfi);mentioning
confidence: 99%